Adaptive fuzzy filter algorithm for LEO communication channel estimation - ZHUO Yong-ning; ZHU Li-dong; WU Shi-qi (Tongxin xuebao)
A novel adaptive LMS filter algorithm based on fuzzy rules was proposed.Through building many fuzzy sets over the space of channel gained value and the increment value of channel gain,in addition to the setting of fuzzy rules,an adaptive algorithm incorporated with human experience was set up,which was adaptive to the timevaring character-istics of LEO satellite channel.The results of the simulation validate the algorithm.